Penerapan Metode Moora Terhadap Pemilihan Jurusan Di Perguruan Tinggi - Lauryn, Maya Selvia; Ibrohim, Muhammad (Jurnal Ilmiah Sains dan Teknologi, 2024)
Universities are institutions providing higher education. Choosing a major in higher education is certainly influenced by many factors. These factors include internal factors and external factors. These internal factors come from the prospective students themselves. On the other hand, there are also external factors that influence the choice of major in higher education, whether from parents or friends. Therefore, a decision support system is needed in determining the appropriate major. The method used is the Multi-Objective Optimization by Ratio Analysis Method. The stages in developing a decision support system for selecting majors are data collection, MOORA calculations to see the relationship between criteria and alternatives, the final stage is testing to validate the results using manual and system calculations. The result of this research is that the decision support system for selecting a major can recommend decision makers in choosing a major.